Las preguntas que plantean los docentes para evaluar competencias en el área de Lengua y Literatura - Castillo Cordero, Anahí Guadalupe (2023)
The purpose of this research is analyze the approach of the questions that teachers design to assess competences in the subject Languague and Literature of Unit Educative “Rosa Herlinda García de García”. A qualitative approach methodology was used of descritvite type; a semi-estructured interview was applied to two teachers in the área of Lengua and Literature, Followed, by a checklist to analyze twenty six questions based on the characteristics of questions to assess competencies; contextualized, productive , complex and using the ordinal type Likert scale with three values: good , regular and bad; Finally, was used a comparison list to compare the quality of the questions with the average grades of the students. The results determined that, of the 26 questions analyzed, 19 are of Regular scale because evaluate productivity and complexity, but do not have context, 2 questions are Good because are productive, complex and contextualized and 10 questions are Bad because do not meet any of the characteristics. The 1st, 2nd, and 3rd grade questionnaires to assess competencies meet only one of the two assessment indicators and in the grades there is a relationship determined by the quality of the question. In conclusion, from the teaching perspective, essential elements such as macro-skills and cognitive and technical aspects are considered for the question construction process; however, in practice they partially evaluate the competencies. Therefore, the results of the applied questionnaires cannot be taken as evidence of competency learning, since the questions focus on evaluating only the productive section and neglect the contextualized and complex aspects. Keywords: Language and Literature, Summative Assessment, Written Exams, Types of Assessment